The Sociolinguistics Study of Varieties Addressing System in Bima-Dompu Society - Rusdin, Rusdin (NUANSA, 2017)
The aim of this paper is to explore the using of addressing system on their name in Bima society based on their social status in their social interaction. This study focusing on specific detail of addressing system name using around the social class of (suku mbojo) Bimaness  (e.g. Dae, dae, Ruma, Muma, Papi, Uma, Ince, Lalu, Lala, Rato, Tati, Teta, Dade, Tato, Uba, Pua, and Ama Kaâu dan Ina Kaâu). Those names have constructed their status in social interaction based on their relatives and kingdomâs breeds. The writer using library research based on the data found on the resources. In collecting the data focus only at Suku mbojo (Bima-Dompu) society. In conclusion the data result there are 17 addressing system using by Suku mbojo in their social life.